Harnessing Fire with AI and Drones: A Holistic Approach to Wildfire Damage in South Korea - Sim, Jiwoo (Eximia, 2025)
The beginning of spring 2025 brought South Korea its worst wildfires which caused extensive environmental damage and fatal human losses and permanent destruction of cultural heritage. The wildfires demonstrated South Korea’s rising exposure to climate change-driven disasters in an unprecedented way. South Korea needs to develop urgent wildfire prevention and detection and management strategies because climate change continues to accelerate at a dangerous rate. The research examines the factors that increase wildfire occurrence and intensity through rising temperatures and extended droughts and poor land management practices. The paper assesses innovative technological solutions which show promising outcomes for wildfire management. The research explores experimental drone technology and artificial intelligence systems which improve wildfire detection speed and precision while enhancing suppression effectiveness. The analysis examines recent studies and real-world implementation cases to demonstrate both the advantages and constraints of these innovative solutions. The research shows that technological progress by itself does not solve wildfire risks effectively. Innovation needs to form part of an integrated system which combines climate-smart forestry with ecological restoration and sustainable land-use planning. The study determines which strategies work best for South Korea while stressing the requirement for an urgent coordinated framework that unites advanced technologies with climate-responsive forestry practices. An integrated system enhances disaster readiness and response capabilities and builds long-term resistance against increasing wildfire threats.